Neuromuscular Complications of COVID-19: Evidence from the Third Year of the Global Pandemic - Suh, Joome; Amato, Anthony (Seminars in Neurology, 2023)
Accumulating evidence in the third year of the global pandemic suggests that coronavirus disease 2019 (COVID-19) can cause neuromuscular complications during or after the acute phase of infection. Direct viral infection and immune-mediated mechanisms have been hypothesized. Furthermore, in patients with underlying autoimmune neuromuscular diseases, COVID-19 infection may trigger a disease flare. COVID-19 vaccines appear to be safe and effective at preventing severe illness from COVID-19. Certain vaccines are associated with an increased risk of Guillain-Barré syndrome and possibly Bell's palsy, but the absolute incidence is low, and benefits likely outweigh the risks. Newer prophylactic therapies and treatments are also becoming available for patients who may not mount a sufficient response to vaccination or have contraindications. In this article, we discuss the current available evidence on neuromuscular complications of COVID-19 and clinical considerations regarding vaccination.
Keywords: COVID-19; SARS-CoV-2; neuromuscular; Gullain-Barre syndrome; myasthenia; myositis; immune-mediated necrotizing myopathy